Intracranial volume (ICV) in isolated sagittal craniosynostosis measured by 3D photocephalometry: A new perspective on a controversial issue. Issue 5 (May 2016) - Seeberger, R.; Hoffmann, J.; Freudlsperger, C.; Berger, M.; Bodem, J.; Horn, D.; Engel, M.
Abstract: Background: There are still controversies regarding the intracranial volumes in patients with isolated sagittal craniosynostosis compared to a healthy population. This study aimed to compare the intracranial volume of children with sagittal synostosis and scaphocephaly to an age- and gender-matched control cohort using three-dimensional (3D) photogrammetry. Methods: 62 boys and nine girls with sagittal craniosynostosis were included in this study. The intracranial volume was measured at the first clinical presentation. However, 3D photogrammetry was performed at children not younger than 3 months. The 3D photogrammetric data of 547 healthy boys and 287 healthy girls between the ages of 3–10 month was analyzed to establish an age- and gender-matched control group. Results: Male patients with sagittal synostosis showed a significantly reduced intracranial volume compared to the reference group. For female patients, the intracranial volume was slightly lower compared to the norm group, but not significantly. Conclusions: Male children with sagittal synostosis showed significantly decreased intracranial volume between the age of 3 and 10 months compared to an age- and gender-matched control group. Female patients in the same age group presented a lower intracranial volume compared to the norm group. Measuring intracranial volume using 3D photogrammetry is a comparable and valuable alternative to CT scans that leads to a significant reduction of radiation exposure to the growing brain.